2012
DOI: 10.1016/j.neuroimage.2012.01.117
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity in addiction: Lessons learned and a road ahead

Abstract: Despite intensive scientific investigation and public health imperatives, drug addiction treatment outcomes have not significantly improved in more than 50 years. Non-invasive brain imaging has, over the past several decades, contributed important new insights into the neuroplastic adaptations that result from chronic drug intake, but additional experimental approaches and neurobiological hypotheses are needed to better capture the totality of the motivational, affective, cognitive, genetic and pharmacological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

46
444
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 431 publications
(492 citation statements)
references
References 181 publications
(275 reference statements)
46
444
2
Order By: Relevance
“…We observed that 31% of the patients with generalized motor PNES reported substance abuse, whereas none of the patients with non-motor PNES had such a history. A previous review suggested that brain circuit connectivity may explain specific neurobiological substrates underlying psychological dysfunctions associated with reward, affective and cognitive processing often observed in drug addiction 12 . The temporal relationship between substance abuse and onset of PNES in our patients remains unknown and therefore, we cannot establish a causal relationship.…”
mentioning
confidence: 99%
“…We observed that 31% of the patients with generalized motor PNES reported substance abuse, whereas none of the patients with non-motor PNES had such a history. A previous review suggested that brain circuit connectivity may explain specific neurobiological substrates underlying psychological dysfunctions associated with reward, affective and cognitive processing often observed in drug addiction 12 . The temporal relationship between substance abuse and onset of PNES in our patients remains unknown and therefore, we cannot establish a causal relationship.…”
mentioning
confidence: 99%
“…Nucleus Accumbens (NAc) Orbitofrontal Cortex (OFC) Drug addiction or substance dependence (Koob and Le Moal, 2005)is defined as a multifaceted neuropsychiatric disorder resulting from complex interactions between neurobiological, environmental, genetic and pharmacological variables (Sutherland et al, 2012).It affects both cognitive as well as emotional processes . Furthermore, the compulsive seeking and taking of the drug despite the negative consequences, (including downward social mobility (Denier et al, 2013b)), constitutes its behavioral phenotype (Volkow et al, 2003).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Finally, in need of a contemporary therapya multimodal therapeutic approach is suggested using classical treatment practices along with current neurotechonologies, such as neurofeedback and goal-oriented video-games Keywords:Heroin addiction, resting-state, functional and structural connectivity, small-world properties, behavioral traits of heroin-dependent individuals. Radial Diffusivity (RD) 5 Drug addiction or substance dependence (Koob and Le Moal, 2005)is defined as a multifaceted neuropsychiatric disorder resulting from complex interactions between neurobiological, environmental, genetic and pharmacological variables (Sutherland et al, 2012).It affects both cognitive as well as emotional processes . Furthermore, the compulsive seeking and taking of the drug despite the negative consequences, (including downward social mobility (Denier et al, 2013b)), constitutes its behavioral phenotype (Volkow et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations